Volume 4A: Combustion, Fuels, and Emissions 2018
DOI: 10.1115/gt2018-75553
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Premixed Gas Turbine Combustion System Fuel Flexibility With Increased Hydrogen Consumption in a Renewable Market Place

Abstract: Gas turbine flexibility is key in markets with significant renewable energy resources. Operational load flexibility and fuel flexibility ensure the gas turbine remains competitive in supporting power generation in renewable markets. For applications where heat is required in support of a process industry the gas turbine offers an additional advantage. Alternate fuels such as hydrogen are generated as byproducts from chemical processing plants. Hydrogen also has the ability to be a ‘battery fuel’ as excess ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is confirmed that up to 65% of blended hydrogen by volume with natural gas can be consumed safely without the risk of flashback and with a NO x emission performance below 7 ppm. The FlameSheet TM technology has been demonstrated up to 80% of hydrogen by volume on a single full-scale, full power "can" in a test facility, with low NO x emissions and without the need for a diluent such as nitrogen and without a performance impact [78]. The combustor offers superior turn-down.…”
Section: Aerodynamically Stabilized Combustionmentioning
confidence: 99%
“…It is confirmed that up to 65% of blended hydrogen by volume with natural gas can be consumed safely without the risk of flashback and with a NO x emission performance below 7 ppm. The FlameSheet TM technology has been demonstrated up to 80% of hydrogen by volume on a single full-scale, full power "can" in a test facility, with low NO x emissions and without the need for a diluent such as nitrogen and without a performance impact [78]. The combustor offers superior turn-down.…”
Section: Aerodynamically Stabilized Combustionmentioning
confidence: 99%
“…Recently, hydrogen fuel was tested in a trapped-vortex combustor that generates a vortex aerodynamically instead of geometrically [13]. It is further stated that fuel that contains 65% hydrogen by volume is able to burn in this combustor with low NO X emissions without diluting the fuel blend [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…An optimization of the spark advance and of the EGR rate may help to find a more satisfactory trade-off between these opposite trends, as demonstrated by Dimopoulos et al 50 In recent years -in the effort promoted by the European Green Deal 30 for the de-carbonization of transport, energy production and other economic sectors -several gas turbine manufacturers, such as Ansaldo Energia Switzerland, 51 Power Systems Mfg. and AES Eurasia, 52 Mitsubishi Heavy Industries 53 and Snam and Baker Hughes, 54 have developed gas turbines able to burn H 2 -CNG blends and pure H 2 .…”
Section: Introductionmentioning
confidence: 99%